ANALISIS PENERAPAN PENYUSUNAN LAPORAN KEUANGAN PADA PT. PEJANTAN TANGGUH ABADI BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK-ETAP) - -, Isnani - (EKONOMIA, 2019)
This study aims to determine and analyze the components ofSAK ETAP. financial statements, balance sheet items and reports on income statement at PT. Pejantan Tangguh Abadi based on SAK ETAP and what are the components of financial statements, balance sheet report items and income statement prepared by PT. Pejantan Tangguh Abadi is in accordance with the provisions of SAK ETAP. The theory used in this study is financial accounting which is a financial information about an entity that the process of preparing financial statements for general purpose oriented to the reporting of external parties. The hypothesis presented is the components of financial statements, balance sheet items, income statements not yet in accordance with SAK ETAP The analytical tool used in this study is comparative method that is a method that compares the standard practice of accounting SAK ETAP with the financial statements of PT. Pejantan Tangguh AbadiThe results of the analysis can be concluded that the components of the financial statements presented not yet in accordance with the criteria value 40% hypothesis testing is accepted the preparation of balance sheet items that are presented is in accordance with the value of the criteria 70% hypothesis testing is rejected and the preparation of income statements reports are presented very suitable to the criteria value of 80% hypothesis testings rejectedThe conclusions of this study are the componets of the financial statements are not yet appropriate, the previously proposed hypothesis is accepted, the preparation of the balance sheet report is appropriate, the previously hypothesis is rejected and the preparation of the income statement items is appropriate, the previously proposed hypothesis is rejected.